Kingship and Polity on the Himalayan Borderland: Rajput Identity during the Early Colonial Encounter - Moran, Arik (Asian Borderlands, 2019)
This book explores the modern transformation of state and society in the Indian Himalaya. Centred on three Rajput-led kingdoms during the transition to British rule (c. 1790-1840) and their interconnected histories, it demonstrates how border making practices engendered a modern reading of 'tradition' that informs communal identities to date. By revising the history of these mountain kings on the basis of extensive archival, textual, and ethnographic research, it offers an alternative to popular and scholarly discourses that grew with the rise of colonial knowledge. This revision ultimately points to the important contribution of borderland spaces to the fabrication of group identities.